Control architecture of survivable multi-domain optical networks - He, He (University of Ottawa (Canada), 2011)
Optical networks have been widely adopted as the transport network in research industry for years. To better utilize the high speed benefit of optical transport networks, control architecture have become the focus of research in recent years. In this thesis, I have developed a control plane architecture integrated with a set of algorithms, schemes and protocols. Based on the two-level inter-domain and intra-domain hierarchical control architecture, I proposed an inter-domain routing algorithm, ring-based topology aggregation scheme and modified RSVP-TE signalling protocol. This thesis aims to provide an efficient control plane architecture in terms of inter-domain routing, intra-domain routing, topology aggregation and signalling.
Keywords: Engineering, Electronics and Electrical.